Functional characterization and physiological roles of the single Shaker outward K+ channel in Medicago truncatula. (2nd March 2020) - Drain, Alice; Thouin, Julien; Wang, Limin; Boeglin, Martin; Pauly, Nicolas; Nieves‐Cordones, Manuel; Gaillard, Isabelle; Véry, Anne‐Aliénor; Sentenac, Hervé
Summary: The model legume Medicago truncatula possesses a single outward Shaker K + channel, whereas Arabidopsis thaliana possesses two channels of this type, named AtSKOR and AtGORK, with AtSKOR having been shown to play a major role in K + secretion into the xylem sap in the root vasculature and with AtGORK being shown to mediate the efflux of K + across the guard cell membrane, leading to stomatal closure. Here we show that the expression pattern of the single M. truncatula outward Shaker channel, which has been named MtGORK, includes the root vasculature, guard cells and root hairs. As shown by patch‐clamp experiments on root hair protoplasts, besides the Shaker‐type slowly activating outwardly rectifying K + conductance encoded by MtGORK, a second K + ‐permeable conductance, displaying fast activation and weak rectification, can be expressed by M. truncatula . A knock‐out (KO) mutation resulting in an absence of MtGORK activity is shown to weakly reduce K + translocation to shoots, and only in plants engaged in rhizobial symbiosis, but to strongly affect the control of stomatal aperture and transpirational water loss. In legumes, the early electrical signaling pathway triggered by Nod‐factor perception is known to comprise a short transient depolarization of the root hair plasma membrane. In the absence of the functional expression of MtGORK, the rate of the membrane repolarization is found to be decreased by a factor of approximately two. This defect was without any consequence on infection thread development and nodule production in plants grown in vitro, but a decrease in nodule production was observed in plants grown in soil. Significance Statement: MtGORK, a voltage‐gated outwardly rectifying Shaker K + channel, is the single counterpart in Medicago truncatula of the two channels of this type in Arabidopsis, and its expression pattern overlaps those of these two channels. Surprisingly, it weakly contributes to K + secretion into the xylem sap, but plays a major role in K + release from guard cells upon stomatal closure and in shaping the early electrical signal triggered by Nod factor perception in root hairs.